2022
DOI: 10.1177/00219983211066991
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic acid and polyhydroxybutyrate coating on hemp fiber: Its effect on hemp fiber reinforced epoxy composites performance

Abstract: The present research work investigated the influence of biodegradable polymer coatings of hemp fiber on the structural, water absorption, mechanical and tribological properties of hemp fiber and hemp fiber reinforced epoxy composites (HFREC). Hemp fibers were initially treated with sodium hydrogen carbonate and then coated with biodegradable polymers like polyhydroxybutyrate (PHB) and polylactic acid (PLA). SEM images of the coated fibers showed a visible change in fiber surface and improvement in surface roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…46,47 This may be the possible reason for better wear resistance of filler reinforced composites. 48 Among all the wear tested composite samples at different sliding speed, EFREC shown the best wear performance followed by FREC and EREC. The hybrid composite (EFREC) developed might have the proper amount of eggshell and fish scale in the epoxy matrix which may contributed to more uniform dispersion of these filler particles in the epoxy matrix than EREC and FREC.…”
Section: Tribological Propertiesmentioning
confidence: 88%
“…46,47 This may be the possible reason for better wear resistance of filler reinforced composites. 48 Among all the wear tested composite samples at different sliding speed, EFREC shown the best wear performance followed by FREC and EREC. The hybrid composite (EFREC) developed might have the proper amount of eggshell and fish scale in the epoxy matrix which may contributed to more uniform dispersion of these filler particles in the epoxy matrix than EREC and FREC.…”
Section: Tribological Propertiesmentioning
confidence: 88%
“…This is due to the polymeric matrix's hydrophobic nature, which decreases their hydrophilic character. Similarly, Behera et al [27] performed PHB and PLA coatings on hemp fibers, and observed greater water absorption resistance with coated fibers than uncoated fibers. In terms of specific results, cellulose showed faster water absorption, reaching 99% at 120 h, while coconut fiber reached 97%.…”
Section: Characterization Of the Biomaterialsmentioning
confidence: 92%
“…Samples of each material were immersed in water for different periods, recording the weight change at 24-h intervals. For the test, 0.6 g of each material was added to 5 mL of water, following the methodology proposed by Behera et al [27]. The percentage of water absorption was calculated using Equation (1):…”
Section: Characterization Of Composite Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface viscosity of the material decreased, mostly due to the strong bond between the treated fibre and the matrix. This led to the development of a lubricant layer that prevents material loss and reduces the friction coefficient [49][50][51]. Figure 10(B) indicates that the highest COF obtained for untreated JFREC is 0.57 at a sliding speed of 2.5 m s −1 and the lowest COF is obtained for ST JFREC is 0.41 at a sliding speed of 1 m s −1 .…”
Section: Coefficient Of Frictionmentioning
confidence: 99%